A Review of Three Simple Plant Models and Corresponding Statistical Tools for Basic Research in Homeopathy - Lucietta Betti; Grazia Trebbi; Michela Zurla; Daniele Nani; Maurizio Peruzzi; Maurizio Brizzi (The Scientific World Journal)
In this paper, we review three simple plant models (wheat seed germination, wheat seedling growth, and infected tobacco plants) that we set up during a series of experiments carried out from 1991 to 2009 in order to study the effects of homeopathic treatments. We will also describe the set of statistical tools applied in the different models. The homeopathic treatment used in our experiments was arsenic trioxide (As2O3) diluted in a decimal scale and dynamized. Since the most significant results were achieved with the 45th decimal potency, both for As2O3 (As 45x) and water (W 45x), we here report a brief summary of these results. The statistical analysis was performed by using parametric and nonparametric tests, and Poisson distribution had an essential role when dealing with germination experiments. Finally, we will describe some results related to the changes in variability, which seems to be one of the targets of homeopathic treatment effect.